Surviving disaster how the brain works under extreme duress - Ripley, Amanda; Keep, Lennlee; Keep, Lennlee; Ripley, Amanda.|tUnthinkable (PBS Distribution, 2012)
Sociologists, neuroscientists, psychologists and survivors have found that the way that people behave in a crisis is very predictable. By combining the stories of survivors with research into how the brain works under extreme duress, it brings light into civilization's darkest moments.